2003
DOI: 10.1002/ijc.11436
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma MMP‐2 and MMP‐9 levels as a surrogate for tumour expression in colorectal cancer patients

Abstract: Matrix metalloproteinases, and notably the gelatinases MMP-2 and MMP-9, have important roles in tumour invasion, metastasis and angiogenesis. Our study investigates the distribution of MMP-2 and MMP-9 in colorectal cancer, the correlation with plasma levels, changes following surgical resection and whether plasma levels reflect clinical staging and disease course. MMP-2 and MMP-9 expression in 48 colorectal tumours and 13 adenomatous polyps was analysed by RT-PCR, immunohistochemistry, and quantified by ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 25 publications
0
90
2
7
Order By: Relevance
“…The positive immunostaining for MMP-9 did not, however, show any significant association with plasma concentrations of MMP-9. Tutton et al 40 have also reported that MMP-9 expression is significantly increased in colorectal cancer tissues, predominantly in the stroma of the tumor, and that plasma levels of MMP-9 are significantly elevated at all stages in colorectal cancer patients, but any correlation between tissue and circulating levels of MMP-9 was not reported. A statistically significant difference was found in this study between the mean values of serum MMP-9 immunoreactive protein in HNSCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The positive immunostaining for MMP-9 did not, however, show any significant association with plasma concentrations of MMP-9. Tutton et al 40 have also reported that MMP-9 expression is significantly increased in colorectal cancer tissues, predominantly in the stroma of the tumor, and that plasma levels of MMP-9 are significantly elevated at all stages in colorectal cancer patients, but any correlation between tissue and circulating levels of MMP-9 was not reported. A statistically significant difference was found in this study between the mean values of serum MMP-9 immunoreactive protein in HNSCC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MMP-2 and MMP-9 has been confirmed in colorectal cancer (3)(4)(5) and gastric cancer (6)(7)(8). Increased levels of MMP-2 and MMP-9 in patients with colorectal and gastric cancer were detected in serum (9,10), plasma (3,9), and tissue (3,11,12).…”
Section: Introductionmentioning
confidence: 89%
“…Increased levels of MMP-2 and MMP-9 in patients with colorectal and gastric cancer were detected in serum (9,10), plasma (3,9), and tissue (3,11,12). Different techniques were utilized for the determination of MMP-2 and MMP-9 including gelatin zymography (11,13), enzyme linked immunosorbant assay (ELISA) (3,14), immunohistochemical techniques (15), in situ hybridization (2) and reverse transcriptasepolymerase chain reaction (3).…”
Section: Introductionmentioning
confidence: 99%
“…Th ey wanted to discover whether plasma levels are a refl ection of the clinical staging and the development of the disease. Th eir results showed that MMP-2 plasma levels were considerably elevated in patients with CRC; they considerably decreased aft er surgical resection of the tumour, and MMP-9 serum levels were considerably elevated in all stages of the disease in CRC patients, while they decreased aft er the surgical resection of the neoplasm (21). On the contrary, the Ruokolainen's investigation for the prognostic role of the MMP-2 and Maurel, Nadal, Garcia-Albeniz et al examined the MMP-7 serum levels in 87 healthy patients and in 120 CRC patients in order to determine the serum level prognostic signifi cance of this enzyme.…”
Section: Discussionmentioning
confidence: 96%